2009
DOI: 10.1002/pros.20958
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Type A Inhibits the Growth of LNCaP Human Prostate Cancer Cells In Vitro and In Vivo

Abstract: BTA inhibits the growth of LNCaP human PCa cells in vitro and in vivo. These findings indicate that intra-prostatic BTA injections to treat BPH are unlikely to promote the growth of co-existing infra-clinical PCa foci in men. A potential inhibitory effect of BTA on the growth of human PCa should be further studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 29 publications
2
40
2
1
Order By: Relevance
“…The role of SV2 in breast cells could be associated to secretory nature of mammary glands, and may interact with other vesicle proteins such as synaptobrevin, which is essential for secretion but not for the development of synaptic process (Ahnert-Hilger et al, 1996), however, the SV2 role in cancer is not clear, although it is already reported in others types of cancer, for instance, brain (de Groot et al, 2010;, pancreas (Jakobsen et al, 2002), gastrointestinal tract (Jakobsen et al, 2002;Bumming et al, 2007 ), liver (Hanoun et al, 2010), bladder (Coelho et al, 2010), prostate (Karsenty et al, 2009) and adrenals (Li et al, 1999) tumors among others, where SV2 has already been proposed as molecular and transdifferentiation marker of neural nature (Nilsson et al, 2004;Zhang et al, 2010). This is possible because in the cancerous state the terminal differentiation to the anticipated cellular type is altered and the phenomena of lineage infidelity that is associated with the ability of cancer cells to transdifferentiate, occurs in different cancer types and occur in breast cancer (Zhang et al, 2010); thus, it is a commune phenomenon that cancer cell turns-off/-on non-habitual genes changing the ontogeny to evade the immune system and hold the linage independence.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The role of SV2 in breast cells could be associated to secretory nature of mammary glands, and may interact with other vesicle proteins such as synaptobrevin, which is essential for secretion but not for the development of synaptic process (Ahnert-Hilger et al, 1996), however, the SV2 role in cancer is not clear, although it is already reported in others types of cancer, for instance, brain (de Groot et al, 2010;, pancreas (Jakobsen et al, 2002), gastrointestinal tract (Jakobsen et al, 2002;Bumming et al, 2007 ), liver (Hanoun et al, 2010), bladder (Coelho et al, 2010), prostate (Karsenty et al, 2009) and adrenals (Li et al, 1999) tumors among others, where SV2 has already been proposed as molecular and transdifferentiation marker of neural nature (Nilsson et al, 2004;Zhang et al, 2010). This is possible because in the cancerous state the terminal differentiation to the anticipated cellular type is altered and the phenomena of lineage infidelity that is associated with the ability of cancer cells to transdifferentiate, occurs in different cancer types and occur in breast cancer (Zhang et al, 2010); thus, it is a commune phenomenon that cancer cell turns-off/-on non-habitual genes changing the ontogeny to evade the immune system and hold the linage independence.…”
Section: Discussionmentioning
confidence: 99%
“…SV2 expression can have a double importance as cancer molecular marker (Zhang et al, 2010) and therapeutic use in malignity due SV2 leads the entry of BoNTA, which has anti-proliferative, pro-apoptotic and quimiodenervation functions in prostate cancer (Arnon et al, 2001;Dong et al, 2006;Choi et al, 2007;Karsenty et al, 2009;Hanoun et al, 2010;Zhenzhen et al, 2012) that could be extrapolate to breast tumors. BoNTA is recognized by SV2 receptors in neurons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations